A strident girl. Issue 4 (25th October 2019) - Corrias, Francesca; Gesuete, Valentina; Murru, Flora Maria; Maschio, Massimo; Barbi, Egidio
Abstract : A 12-year-old girl was referred with a 7-month history of episodes of dyspnoea, stridor and a sense of chest constriction during physical exercise. These were self-limiting and never occurred at night. Physical examination was normal. An initial diagnosis of vocal cord dysfunction was made. Spirometry showed a plateau of forced expiratory flow, with a truncated aspect of the expiratory phase (figure 1 ). Six weeks later she described occasional dysphagia with solid foods. The barium swallow, performed only in anteroposterior projection, did not show oesophageal dilation. A bronchoscopy showed extrinsic compression of the middle lower third of the trachea and the right main bronchus. A chest CT scan was performed (figures 2 and 3 ). Questions: What is your diagnosis? Persistent vocal cord dysfunction Achalasia Vascular ring Asthma What is the gold standard for diagnosis of VR? ECG Chest radiograph CT and/or MRI Bronchoscopy How should this patient be treated? Surgical correction Video-assisted thoracoscopy Decompression of the oesophagus with a nasogastric tube Inspiratory muscle training and ipratropium bromide inhaler What signs in the history pointed away from vocal cord dysfunction? Dysphagia with solid food was present. The episodes of dyspnoea and stridor never occurred at night. The episodes arose mainly on exertion. The episodes of dyspnoea and stridor were self-limiting. Answers can be found on page 2.